Influence of Hepatitis B Virus X and Core Promoter Mutations on Hepatocellular Carcinoma among Patients Infected with Subgenotype C2 - Shinkai, Noboru (American Society for Microbiology, 2007)
Hepatitis B virus (HBV) genotypes/subgenotypes and their related mutations in the HBV genome have been reported to be associated with hepatocellular carcinoma (HCC). To determine the HCC-associated mutations of the HBV genome in the entire X, core promoter, and precore/core regions, a cross-sectional control study was conducted comparing 80 Japanese patients infected with HBV C2 and suffering from HCC with 80 age-, sex-, and hepatitis B e antigen (HBeAg) status-matched patients without HCC (non-HCC group). Each HBeAg-positive group (31 with HCC; 29 without HCC) and HBeAg-negative group (49 with HCC; 51 without HCC) was also matched with respect to age and sex. The C1479, T1485, H1499, A1613, T1653, V1753, T1762/A1764, and A1896 mutations were frequent in this population. The prevalences of the T1653 mutation in the box α region and the V1753 and T1762/A1764 mutations in the basal core promoter region were significantly higher in the HCC group than in the non-HCC group (56% versus 30%, 50% versus 24%, and 91% versus 73% [P = 0.0013, P = 0.0010, and P = 0.0035, respectively]). The platelet count was significantly lower for the HCC group than for the non-HCC group (10.7 × 10(4) ± 5.1 × 10(4) versus 17.3 × 10(4) ± 5.1 × 10(4) platelets/mm(3) [P < 0.0001]). Regardless of HBeAg status, the prevalence of the T1653 mutation was higher in the HCC group (52% versus 24% [P = 0.036] for HBeAg-positive patients and 59% versus 33% [P = 0.029] for HBeAg-negative patients). In the multivariate analysis, the presence of T1653, the presence of V1753, and a platelet count of ≤10 × 10(4)/mm(3) were independent predictive factors for HCC (odds ratios [95% confidence intervals], 4.37 [1.53 to 12.48], 7.98 [2.54 to 25.10], and 24.39 [8.11 to 73.33], respectively). Regardless of HBeAg status, the T1653 mutation increases the risk of HCC in Japanese patients with HBV/C2.